Candidaemia in haematological malignancy patients from a SEIFEM study: Epidemiological patterns according to antifungal prophylaxis. Issue 9 (3rd July 2020) - Posteraro, Brunella; De Carolis, Elena; Criscuolo, Marianna; Ballanti, Stelvio; De Angelis, Giulia; Del Principe, Maria Ilaria; Delia, Mario; Fracchiolla, Nicola; Marchesi, Francesco; Nadali, Gianpaolo; Picardi, Marco; Piccioni, Anna Lina; et al.
Abstract: Background: Candidaemia is an important infectious complication for haematological malignancy patients. Antifungal prophylaxis reduces the incidence of candidaemia but may be associated with breakthrough candidaemia. Objective: To analyse the Candida species' distribution and relative antifungal susceptibility profiles of candidaemia episodes in relation to the use of antifungal prophylaxis among Italian SEIFEM haematology centres. Methodology: This multicentre retrospective observational SEIFEM study included 133 single‐species candidaemia episodes of haematological malignancy patients for whom antifungal susceptibility testing results of blood Candida isolates were available between 2011 and 2015. Each participating centre provided both clinical and microbiological data. Results: Non‐ Candida albicans Candida (NCAC) species were the mostly isolated species (89, 66.9%), which accounted for C parapsilosis (35, 26.3%), C glabrata (16, 12.0%), C krusei (14, 10.5%), C tropicalis (13, 9.8%) and uncommon species (11, 8.3%). C albicans caused the remaining 44 (33.1%) episodes. Excluding 2 C albicans isolates, 23 of 25 fluconazole‐resistant isolates were NCAC species (14 C krusei, 6 C glabrata, 2 C parapsilosis and 1 C tropicalis ). Fifty‐six (42.1%) of 133 patients developed breakthrough candidaemia. Systemic antifungal prophylaxis consisted of azoles, especially fluconazole and posaconazole, in 50 (89.3%) of 56 patients in whom a breakthrough candidaemia occurred. Interestingly, all these patients tended to develop a C krusei infection (10/56, P = .02) or a fluconazole‐resistant isolate's infection (14/50, P = .04) compared to patients (4/77 and 10/77, respectively) who did not have a breakthrough candidaemia. Conclusions: Optimisation of prophylactic strategies is necessary to limit the occurrence of breakthrough candidaemia and, importantly, the emergence of fluconazole‐resistant NCAC isolates' infections in haematological malignancy patients.